2014
DOI: 10.1038/mtm.2013.8
|View full text |Cite
|
Sign up to set email alerts
|

Adipose tissue insulin receptor knockdown via a new primate-derived hybrid recombinant AAV serotype

Abstract: Adipose tissue plays an essential role in metabolic homeostasis and holds promise as an alternative depot organ in gene therapy. However, efficient methods of gene transfer into adipose tissue in vivo have yet to be established. Here, we assessed the transduction efficiency to fat depots by a family of novel engineered hybrid capsid serotypes (Rec1~4) recombinant adeno-associated viral (AAV) vectors in comparison with natural serotypes AAV1, AAV8, and AAV9. Rec2 serotype led to widespread transduction in both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(56 citation statements)
references
References 42 publications
0
56
0
Order By: Relevance
“…injected to male BALB/c mice at a dose of 2 × 10 10 vg per mouse, which is similar to the doses previously used in i.v. injection, oral administration, or direct fat pad injection 7, 12. 2 weeks post-Rec2 administration, mice were subjected to in vivo bioluminescence measurement, and strong luciferase activity was observed primarily in the abdomen (Figure 1A).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…injected to male BALB/c mice at a dose of 2 × 10 10 vg per mouse, which is similar to the doses previously used in i.v. injection, oral administration, or direct fat pad injection 7, 12. 2 weeks post-Rec2 administration, mice were subjected to in vivo bioluminescence measurement, and strong luciferase activity was observed primarily in the abdomen (Figure 1A).…”
Section: Resultsmentioning
confidence: 99%
“…A few groups have targeted adipose tissue with naturally occurring AAV serotypes by direct injection to fat depots often requiring high doses 3, 4, 5. We previously report that an engineered hybrid serotype Rec2 displays superior transduction of both brown adipose tissue (BAT) and subcutaneous WAT (SAT) compared to AAV1 or AAV8 7 . Direct injection of Rec2 vector at a moderate dose (1 × 10 9 to 1 × 10 10 vg per fat depot) is sufficient to modulate the function of the targeted fat depot (BAT or SAT) and result in systemic metabolic changes 7, 8, 9, 10.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…rAAV serotype 1 vectors carrying TrkB.T1, BDNF, or YFP were packaged and purified as described elsewhere (35). An engineered hybrid rAAV serotype Rec2 vector carrying Cre or YFP were packaged and purified as described previously (36).…”
Section: Ee Protocolmentioning
confidence: 99%
“…We reported that injection of a novel engineered rAAV serotype Rec2 carrying Cre recombinase fused with GFP (Cre/GFP) to the BAT and WAT of insulin receptor flox/flox mice efficiently knocked down insulin receptor expression resulting in dysfunction of transduced fat pad and impaired whole body glucose tolerance (36). To avoid high level of Cre-associated toxicity in the hypothalamus, we performed a titer titration experiment in wild-type mice and found bilateral injection of Rec2-Cre/GFP at the dose of 1 3 10 9 vg per site showed no difference of body weight or food intake compared with mice receiving Rec2-YFP (data not shown).…”
Section: Hypothalamic Knockdown Of Vgf Leads To Metabolic Disturbancementioning
confidence: 99%